Biosynthetic Pathways and the Role of the Mas Receptor in the Effects of Angiotensin-(1–7) in Smooth Muscles - Marcio Augusto Fressatto de Godoy; Larissa Pernomian; Ana Maria de Oliveira; Satish Rattan (International Journal of Hypertension)
Ang-(1–7) is produced via degradation of Ang II by the human angiotensin converting enzyme, also known as ACE2. In the cardiovascular system, Ang-(1–7) has been shown to produce effects that are opposite to those of Ang II. These include smooth muscle relaxation and cardioprotection. While the roles of Ang-(1–7) in other systems are currently topic of intense research, functional data suggest a relaxation action in gastrointestinal smooth muscles in a way that corroborates the results obtained from vascular tissues. However, more studies are necessary to determine a relevant role for Ang-(1–7) in the gastrointestinal system. The Ang-(1–7) actions are mediated by a distinct, functional, Ang-(1–7) receptor: the Mas receptor as shown by diverse studies involving site-specific binding techniques, selective antagonists, and targeted gene deletion. This paper provides an overview of the functional role and the molecular pathways involved in the biosynthesis and activity of Ang-(1–7) in diverse systems.